The role of standardisation in future autonomic communication systems - LEWIS, DAVID (IEEE Computer Society, 2008)
This paper examines the potential problems of interoperability in the development and widespread future deployment of autonomic communication systems. It draws on experiences from previous standardization efforts in the communications domain and outlines the new challenges faced in building industrial strength networks that are self-configuring, self-healing, self optimizing, self-protecting, and most importantly, self-governing. It then outlines the work-program being undertaken by the Autonomic Communication Forum and introduces the other papers in this session that present details of these challenges and directions being pursued.
IEEE Workshop on Engineering of Autonomic and Autonomous Systems: 5th : 2008
EASe 2008
PUBLISHED
Keywords: autonomic communication; interoperability; Autonomic Communication Forum